2021
DOI: 10.1016/j.ajem.2021.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic Thrombocytopenic Purpura after Ad26.COV2-S Vaccination

Abstract: The U.S. Food and Drug Administration (FDA) recently issued an Emergency Use Authorization (EUA) for two highly effective Sars-CoV-2 (COVID-19) vaccines from Pfizer-BioNTech and Moderna. More recently, Emergency Use Authorization was granted for the Johnson and Johnson COVID-19 vaccine which uses traditional virus-based. In this vaccine, researchers added the gene for the coronavirus spike protein to modified Adenovirus 26 and named it Ad26.COV2-S. Nearly 7 million doses of the Ad26.COV2-S have been administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 4 publications
1
53
0
1
Order By: Relevance
“…Yocum [9] and Sissa [10] reported women with co-morbidities in a similar age group as our patient presenting with similar symptoms within a month of administration of the Ad26.COV2.S and BNT162b2 mRNA vaccines, respectively, indicating the presence of a possible diagnosis of VIPIT that was treated efficiently with plasmapheresis in both cases. Of note, in the latter case involving BNT162b2, the patient suffered from relapse precisely six days after the second dosage of COVID vaccine, just as in our casealthough our patient never had TTP before.…”
Section: Discussionsupporting
confidence: 75%
“…Yocum [9] and Sissa [10] reported women with co-morbidities in a similar age group as our patient presenting with similar symptoms within a month of administration of the Ad26.COV2.S and BNT162b2 mRNA vaccines, respectively, indicating the presence of a possible diagnosis of VIPIT that was treated efficiently with plasmapheresis in both cases. Of note, in the latter case involving BNT162b2, the patient suffered from relapse precisely six days after the second dosage of COVID vaccine, just as in our casealthough our patient never had TTP before.…”
Section: Discussionsupporting
confidence: 75%
“…has recently been published. 17 The pathophysiology of vaccine-related thrombotic microangiopathies is not entirely clear. Already in 1960, Frick et al reported a TTP episode 24 h after typhoid vaccination, suggesting vaccination as triggering factor.…”
mentioning
confidence: 99%
“…Based on these observations, the vWF/ADAMTS13 imbalance has been proposed to be causally related both to the prothrombotic tendency and to the microvascular pulmonary thrombosis, which subtend to a form of thrombotic microangiopathy (TMA) observed in severe COVID-19 patients. The severe deficiency of ADAMTS13 has also gained attention due to the development of a rare TMA, called immune-mediated thrombotic thrombocytopenic purpura [71,72], caused by the production of anti-ADAMTS13 antibodies, in a limited number of subjects after COVID-19 vaccination. Interestingly, vWF significantly increases with age and in non-0 blood type individuals [73], both risk factors for COVID-19.…”
Section: Discussionmentioning
confidence: 99%